If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -5x + -4 = 0 Reorder the terms: -4 + 9x + -5x = 0 Combine like terms: 9x + -5x = 4x -4 + 4x = 0 Solving -4 + 4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4x = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 4x = 0 + 4 4x = 0 + 4 Combine like terms: 0 + 4 = 4 4x = 4 Divide each side by '4'. x = 1 Simplifying x = 1
| 3w-21=0 | | -3x+15=3x-15 | | 3(3x-3)=36 | | X+36=12 | | 9=5n+4n | | 4x+7x-10=0 | | 3x+7=-3x+2+6x | | 5x+3=4x-5 | | -70-8x=17x+20 | | -7x+4=0 | | 5x^3+4x+1=0 | | -70-8x=106-36x | | -60-9x=10x | | 2(3x-1)=10 | | -9=4y+6 | | -10z-0.5=20z+1.6 | | 2(5-3x)=85-2x | | 5x+7x-12=0 | | 11x-(5x-2)=38 | | -17z-4=-16z-20 | | 1=-4v+13 | | P=b+c+d | | -37-2x=8-7x | | 10-(2x-1)=1-6x | | 9-2(121-64)=36x | | 7v-19=9 | | 2(4x+1)=-12+6 | | 4x-308+x-32+.5x+14= | | -5v-19=7 | | -37-3x=5-9x | | 2=4 | | 17x-7y=-11 |